(untitled) (JOURNAL OF ADVANCES IN AGRICULTURE, 2017)
Cowpea (Vigna unguiculata) is an important crop for people living in the semi-arid tropics where it is used as food, animal feed and forage. Researches related to nutritional status of plants are important, principally in crops commonly grown in nutrient-poor soils. This study aimed to analyze the growth and accumulation/distribution of some micronutrients in cowpea plants submitted to macro and micronutrient deficiency. Cowpea seeds were germinated in grit and after five days, ten uniform seedlings were transferred to complete nutrient solution for an acclimatization period. After three days, the plants were grown in nutrient solution containing all macro and micronutrients or in nutrient solution without N, Ca, K, Mg, P, S, Fe, B or aeration. In all case, omission of mineral nutrients and the aeration caused reductions in the dry mass of cowpea plants, except for B; however, the absence of Ca was the most limiting for plant growth. Interestingly, the root Fe content significantly increased in Mg-, P- and S-deficient plants. Yet, Fe-deficient plants displayed a significant increase in Cu and Mn content, regardless of plant organ. Our data clearly demonstrate that the Ca is the most important nutrient for V. unguiculata growth, followed by N and Fe. The accumulation and partition of Fe, Zn, Cu and Mn in cowpea vary differentially in root, stem and leaf as affected by nutritional deficiency.